Product development of grasshopper pempek as additional food for pregnant woman - Lirizka, Sessy Paramita; Anwar, Faisal; Palupi, Eny (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
The demand for nutritious protein sources for pregnant women is growing, particularly to address malnutrition in Indonesia. Wood grasshoppers (Valanga nigricornis) offer an environmentally sustainable, nutrient-dense protein alternative. This study developed pempek from wood grasshoppers as a food product for pregnant women. A laboratory experiment used a completely randomized design with three formulations varying wood grasshopper and tapioca flour proportions: F1 (75:25 grasshopper:tapioca), F2 (50:50), and F3 (25:75). Organoleptic tests showed greater preference for F1 and F2 over F3; F2 was selected as the best due to its higher protein and iron content. Wood grasshopper pempek (F2) shows potential as a nutritious alternative to improve nutritional adequacy for pregnant women, particularly in meeting protein and iron needs. Future research should examine nutritional enhancement via amino acid modification, such as addition of methionine-rich foods.